Implementation of Rehabilitation of Narcotics Users as Detention According to Article 127 of Law No. 35 of 2009: A Case Study of BNNP Central Java - Widya Oktavia; Benny Sumardiana (Universitas Negeri Semarang, 2026)
This study aims to analyze the criminal law regulation of narcotics users based on Article 127 of Law Number 35 of 2009, examine the practice of implementing inpatient rehabilitation for narcotics users sentenced to one year of imprisonment, and assess whether inpatient rehabilitation may be regarded as a form of detention and its implications for the rights of the defendants. The research employs an empirical legal research method with a descriptive analytical approach. Data were obtained through interviews with investigators from the National Narcotics Agency of Central Java Province, as well as an examination of laws and regulations, legal documents, and related literature. The results of the study indicate that, normatively Article 127 of the Narcotics Law has provided a legal basis for the implementation of medical and social rehabilitation as an alternative to punitive criminal sanctions. However, in practice, the implementation of inpatient rehabilitation is not fully consistent with its rehabilitative purpose. In certain circumstances, it functions in a manner similar to detention during the legal process, particularly due to the absence of a clear time limit and divergent interpretations among law enforcement officials. This condition has implications for potential violations of the rights of defendants who use narcotics, especially the right to personal liberty, adequate medical treatment, and humane treatment. Therefore, consistency in the application of Article 127 is needed in line with the principles of restorative justice and the protection of human rights so that rehabilitation truly functions as an instrument of social recovery and reintegration.